Exploring the Relationship Between Iranian EFL Teachers’ Teaching Style and Multiple Dimensions of Self-Efficacy - Sadoughvanini, Seyedhamed; Yazdanmehr, Elham (Colombian Applied Linguistics Journal, 2026)
Following the social cognitive theory, this cross-sectional, correlational study aimed to explore Iranian English as Foreign Language (EFL) teachers’ preferred teaching style and its effect on their perceived self-efficacy in accomplishing specific classroom tasks. To this aim, Grasha’s Teaching Style Inventory (TSI) and Tschannen-Moran Teachers’ Sense of Efficacy Scale (TSES) were used to test teaching style preferences and self-efficacy. To this aim, 233 EFL teachers from both Iranian public schools and private language institutes were included. Data were analyzed using the chi-square test, one-way ANOVA, and Bonferroni post hoc comparisons. Results showed that facilitator and personal model teaching styles were the two most frequent styles. Regarding participants’ self-efficacy, those who adopted a facilitator teaching style reported the highest scores across all subscales of self-efficacy. Additionally, a statistically significant difference was found between the self-efficacy levels of teachers with facilitator versus formal authority teaching styles (p = 0.000). These findings have important implications for teacher education programs in Iran, highlighting the need for the programs to provide teachers with enough opportunities to develop communicative teaching practices, engage students effectively, and enhance their sense of self-efficacy. Teacher trainers can monitor teachers’ progress in self-efficacy and accordingly modify the teaching methods, to acknowledge teacher psychology involved in teacher practice.